Disease management: definitions, difficulties and future directions - Pilnick Alison; Dingwall Robert; Starkey Ken (The World Health Organization, 2001)
The last decade has seen a wide range of experiments in health care reform intended to contain costs and promote effectiveness. In the USA, managed care and disease management have been major strategies in this endeavour. It has been argued that their apparent success has strong implications for reform in other countries. However, in this paper we ask whether they are so easily exportable. We explain the concepts involved and set the development of managed care and disease management programmes in the context of the USA. The constituent elements of disease management are identified and discussed. Disease management is considered from the perspectives of the major stakeholders in the United Kingdom, and the differences between the models of health care in the United Kingdom's National Health Service and the USA are noted. A review is presented of evaluations of disease management programmes and of the weaknesses they highlight. The prospects for disease management in Europe are also discussed.